Bis(μ-3,5-dinitrobenzoato-κ2O1:O1′)bis(μ-3,5-dinitrobenzoato)-κ3O1,O1′:O1;κ3O1:O1,O1′-bis[(3,5-dinitrobenzoato-κ2O1,O1′)(1,10-phenanthroline-κ2N,N)dysprosium(III)] - Gai-Qing Xi; Ning Ren; Da-Hai Zhang; Chun-Hua Dong; Juan-Juan Hao (Acta Crystallographica Section E, 2011)
In the binuclear title complex, [Dy2(C7H3N2O6)6(C12H8N2)2], the DyIII ions exhibit a distorted monocapped square-antiprismatic geometry and are coordinated by seven O atoms of four 3,5-dinitrobenzoate (DNBA) anions and two N atoms of a phenanthroline ligand. The carboxylate groups of the DNBA anions exhibit three coordination modes: bidentate chelating, bidentate chelating–bridging and tridentate chelating–bridging. The center of the molecule is located on a crystallographic center of inversion.